The impact of an implementation intervention that increased school's delivery of a mandatory physical activity policy on student outcomes: A cluster-randomised controlled trial. Issue 4 (April 2022) - Hall, Alix; Wolfenden, Luke; Shoesmith, Adam; McCarthy, Nicole; Wiggers, John; Bauman, Adrian E.; Rissel, Chris; Sutherland, Rachel; Lecathelinais, Christophe; Brown, Hannah; Trost, Stewart G.; Nathan, Nicole
Abstract: Objectives: Assess the impact of an implementation intervention on student's physical activity, health-related quality of life (HRQoL) and on-task behaviour. Design: A cluster-randomised controlled trial. Methods: Following baseline 61 eligible schools were randomised to a 12-month, implementation intervention to increase teacher scheduling of physical activity, or a waitlist control. Whole school-day and class-time physical activity of students from grades 2 and 3 (~ages 7 to 9) were measured via wrist-worn accelerometers and included: moderate-to-vigorous physical activity, light physical activity, sedentary behaviour and activity counts per minute. Children's health related quality of life (HRQoL) and out-of-school-hours physical activity was measured via parent-proxy surveys. Class level on-task behaviour was measured via teacher self-report surveys. Student and teacher obtained outcomes were measured at baseline and 12-month follow-up. Parent reported outcomes were measured at 12-month follow-up. Linear mixed models compared between group differences in outcomes. Differential effects by sex were explored for student and parent reported outcomes. Results: Data from 2485 students, 1220 parents and >500 teachers were analysed. There was no statistically significant between group differences in any of the outcomes, including accelerometer measured physical activity, out-of-school-hours physical activity, HRQoL, and on-task behaviour. A statistically significant differential effect by sex was found for sedentary behaviour across the whole school day (3.16 min, 95% CI: 0.19, 6.13; p  = 0.028), with females illustrating a greater difference between groups than males. Conclusions: Only negligible effects on student physical activity were found. Additional strategies including improving the quality of teacher's delivery of physical activity may be required to enhance effects.